Opinion Toward Pictorial Warning Label on Alcohol Container: a Case Study of Factory Employees - Pattanasathiankul, Thanapen; Lochid-amnuay, Surasit (Journal of Health Science of Thailand, 2017)
Pictorial warning label on alcohol container is one of the concepts on reducing alcohol consumption in Thailand. This study was a cross-sectional survey research in 370 factory employees. The objectives were to study the opinion toward pictorial warning label on alcohol container and the effects of pictorial warning label toward the subjects’ perceptions of severity disease or hazard, level of fear and intention to reduce alcohol consumption. Data were collected by using questionnaire; and analyzed by descriptive statistics and correlation analysis of factors by Chi-square test. Results showed that most of subjects (41.4%) agreed that the pictorial warning label had effect on intention to reduce or quit alcohol drinking. The picture “disability and death caused by drunk driving” had more profound effect on perceptions of severity disease or hazard, level of fear and intention to reduce alcohol consumption. Level of education, history of alcohol drinking and married status were significantly associated with the effect of pictorial warning label on intention to reduce alcohol consumption (p=0.001, 0.015 and <0.001, respectively). This study indicated that pictorial warning label on the beverage container had effect on alcohol consumption in factory employees. Similar study should be conducted among other groups of the population in order to develop a strong policy on pictorial warning label on alcohol container.